2020
DOI: 10.1002/arcp.1061
|View full text |Cite
|
Sign up to set email alerts
|

Intentions

Abstract: Intentions are one of the most widely used constructs in consumer research. We review over 50 years of research that has helped us understand what intentions are, their antecedents and consequences, and how best to measure and use them as a proxy for or predictor of behavior. We define intentions and differentiate them from other closely relatedly psychological constructs. We review several psychological theories where intentions play a central role and highlight what is known about the strength of the intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 142 publications
(201 reference statements)
0
32
0
4
Order By: Relevance
“…1 This potentially weak connection is often referred to as the "intention-behavior gap," and it is driven in large part by individuals who indicate an intention to complete a behavior but then do not follow through. More recent reviews (e.g., Morwitz and Munz 2020;Sheeran and Webb 2016) have suggested that whereas correlations between intentions and behaviors represent, on average, "medium effect sizes," substantial variances in these effect sizes have been noted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 This potentially weak connection is often referred to as the "intention-behavior gap," and it is driven in large part by individuals who indicate an intention to complete a behavior but then do not follow through. More recent reviews (e.g., Morwitz and Munz 2020;Sheeran and Webb 2016) have suggested that whereas correlations between intentions and behaviors represent, on average, "medium effect sizes," substantial variances in these effect sizes have been noted.…”
mentioning
confidence: 99%
“…Such research clearly has value. For example, considerable early work using the theory of planned behavior focused on distinguishing beliefs and attitudes from intentions (Morwitz and Munz 2020). In these cases, "enhancing realism and utilizing behavioral measures isn't always necessary or even preferred" (Morales et al 2017, p. 467).…”
mentioning
confidence: 99%
“…This index will represent a single trait: intentions to engage in omnichannel retailing through a mobile device. Morwitz and Munz (2021) define intentions as how much a consumer resolves or desires to act in a certain manner. As such, the unidimensional MIX construct is similar to other global scales that tap into behavioral and usage intentions including validated measures of prosocial behavior (Baumsteiger and Siegel, 2019), desires for new products (Lynn and Harris, 1997), social media use (Chintalapati and Daruri, 2017), online innovativeness (Goldsmith, 2001), and digital coupon redemption (Nayal and Pandey, 2020).…”
Section: In the Former Sections (Development Of The MIX Index Andmentioning
confidence: 99%
“…Respondents were disqualified from participation if they purchased less than one fashion product in the past 3 months. It was also imperative to recruit consumers with prior mcommerce and omnichannel shopping experience so that they could understand and respond accurately to the mobile instore activities that would be presented to them in the survey (Hallikainen et al, 2019;Morwitz and Munz, 2021). Therefore, we pre-screened survey respondents based by asking them, "What technology do you use when shopping for fashion products?"…”
Section: Data Collection and Sample Characteristicsmentioning
confidence: 99%
“…Entrepreneurship is a deliberate behavior and therefore entrepreneurial intentions are the foundation of the desire to start a new business. Generally, an intention is defined as the degree to which a person resolves to act in a certain way (Morwitz & Munz 2021). By extension, an entrepreneurial intention is a strong determination to set up a new business venture and willfully plan to do so at some point in the future (Al-Jubari, Hassan & Liñán, 2019).…”
Section: Entrepreneurial Competencies and Intentionsmentioning
confidence: 99%